Fostering the Creative Attitude with Remote Lab Learning Environments: An Essay on the Spirit of Research in Engineering Education - Terkowsky, Claudius; Haertel, Tobias (International Journal of Online and Biomedical Engineering (iJOE), 2013)
Creativity has been proclaimed to be one of the most important 21st century skills. Facing tremendous problems, creativity and innovation were seen as key factors of a knowledge-based society able to cope with ongoing and future problems. As Engineers are addressed to play an important role in facing these challenges, the question arises in which way universities could contribute to educate crea-tive engineers. This slightly provoking essay inducts possible boundary conditions and constraints of fostering creativity in engineering education. Moreover, it presents first results from a small-sample pre-study on higher engineering educa-tion curricula, conducted in the funded German project â??ELLIâ??Excellent Teaching and Learning in Engineering Educationâ?, which suggests a lack of creativity education in the examined curricula. Furthermore, a descriptive analysis of the didactic approach of the finished EU-project â??Pe-TEXâ??Platform for E-Learning and Telemetric Experimen-tationâ? provides information about possibilities of fostering the creative attitude in engineering education by means of remote labs. Finally, the essay resumes with future tasks for the ELLI project and open questions addressing relevant future educational and socio-economic impacts, regarding the role of creativity in engineering education and the pro-fessionalization of engineers.